Keabsahan Hibah kepada Anak Angkat yang Melampaui Sepertiga Harta dalam Perspektif Hukum Islam - Suhibbullah; Laras Shesa; Ahmad Dibul (Kartika: Jurnal Studi Keislaman, 2026)
Hibah (gift) is an instrument of Islamic law that allows the voluntary transfer of property ownership while the grantor is still alive, including to an adopted child who, under sharia, has no blood relation (nasab) or inheritance rights with his or her adoptive parents. The practice of granting a hibah exceeding one-third of the estatethe limit customarily applied to bequests (wasiat) was found in Pasar Lama Village, Lahat Subdistrict, South Sumatra Province, and carries the potential to create friction with the rights of legitimate heirs. This article analyzes this practice and the factors underlying it, and examines the perspectives of Islamic law, the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), and local religious leaders, through a descriptive qualitative approach designed as field research with a juridical-sociological perspective, employing interviews, observation, and documentation analyzed through source triangulation. The findings show that such gifts are driven by emotional closeness, the absence of biological children, and the collective consent of the family, which functions as a mechanism of social legitimacy. The views of religious leaders are divided between a protective paradigm that analogizes hibah to the limits of bequests, and a flexible paradigm that emphasizes the property owner's full discretion (tasarruf). This study concludes that the validity of a hibah exceeding one-third of the estate depends not merely on its amount, but on whether it fulfills the principles of justice, benefit (maslahah), and heirs' consent, in accordance with Article 210 of the KHI, and it recommends strengthening Islamic family law literacy and orderly documentation of gifts to prevent future family disputes